2020
DOI: 10.1101/2020.10.23.20218289
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seroprevalence of SARS-CoV-2 antibodies and associated factors in health care workers: a systematic review and meta-analysis

Abstract: Background: Health care workers (HCWs) represent a high risk population for the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Aim: To determine the seroprevalence of SARS-CoV-2 antibodies among HCWs, and to find out the factors that are associated with this seroprevalence. Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines were applied for this systematic review and meta-analysis. Databases including PubMed/MEDLINE and pre-print services (medRχ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
72
5
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(96 citation statements)
references
References 103 publications
(276 reference statements)
16
72
5
2
Order By: Relevance
“…Our study calculated the pooled seroprevalence of SARS-CoV-2 IgG antibodies among the HCWs 8.6%, which is higher than the general population. Similar meta researches find different seroprevalences in the HCWs, varying from 7% to 11% [15] , [16] , [17] .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Our study calculated the pooled seroprevalence of SARS-CoV-2 IgG antibodies among the HCWs 8.6%, which is higher than the general population. Similar meta researches find different seroprevalences in the HCWs, varying from 7% to 11% [15] , [16] , [17] .…”
Section: Discussionsupporting
confidence: 55%
“…The prevalence of such antibodies from a large-scale serosurvey conducted over four collection periods in the US ranged from less than 1% to 23% [13] . To date, three meta-analyses of antibody prevalence among HCWs have been published, and the presence of IgG and/or IgM antibodies has been found to vary between 8% and 17% globally [15] , [16] , [17] . These articles included pre-print articles as well as accounted IgG and/or IgM antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of seroprevalence studies suggested high risk of SARS-CoV-2 infection among HCW. 2 In contrast, we observed a very low seropositive rate in the staff of NCGM as of July 2020, which was even lower than that among the general population in Tokyo. In a tertile hospital in the US, rate of SARS-CoV-2 infection among HCW was lower than that among the general public in the surrounding region.…”
contrasting
confidence: 61%
“…The prevalence of SARS-CoV-2 antibodies among HCWs which are presumed at higher risk for infection, has been increasingly investigated [ 40 ]. In a meta-analysis of 49 studies including 127,480 health care workers overall seroprevalence of SARS-CoV-2 antibodies was 8.7% (95% CI: 6.7-10.9%) [ 41 ]. Major factors driving seropositivity are the type of hospital setting assessed, the job duties and patient contacts of the HCW, and the intensity of the COVID-19 pandemic in the area [ 42 ].…”
Section: Discussionmentioning
confidence: 99%